Pamięć jako pojęcie sterujące badaniem dziejów języka = Memory as a notion guiding the research into language history - Pastruch, Magdalena (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The author proposes incorporating memory in the set of notions which conduct the research on the history of language. She proves that this category plays a significant role in historiographic narration by showing the examples of some lexicological works.
Keywords: pojęcie sterujące; pamięć; leksykologia historyczna; guiding notion; memory; historical lexicology